Teaching identity into Atendimento Educacional Especializado context: constitution and idiosyncrasies - Solon, Thiago Falcão; Falcão, Giovana Maria Belém (Série-Estudos - Periódico do Programa de Pós-Graduação em Educação da UCDB, 2023)
The paper aims at reflecting on the constitution of Atendimento Educacional Especializado (AEE) teachers’ identity, highlighting aspects and idiosyncrasies intertwined in this process. The text, in the format of a theoretical essay, discusses the concept of teaching identity, as well as the characteristics and specificities relating to identity constitution in the context of AEE. Results allowed to conclude that dealing with AEE teachers’ identity means reflecting on the complexity of factors that involve the constitution of these subjects, encompassing social, personal, and professional aspects. AEE teacher’s work deserves some attention as well, once they are perceived as the ones responsible for contributing to the inclusion of students with disabilities at school. It has been challenging and, above all, a historical process since there is a risk of passive adherence into the way AEE teacher was defined over the time. Therefore, expanding this debate is fundamental so that a more autonomous, critical, and emancipated teaching identity in the context of AEE can be considered.